Teaching Algorithms with the Use of a Web-Based Scripted Collaboration Environment and Algorithm Visualization Tool: Results from a Case Study - Foutsitzis, C G; Demetriadis, S N (2010 2nd International Conference on Intelligent Networking and Collaborative Systems, 2010)
In this paper we present data from a case study examining the influence of employing a reciprocal peer tutoring script in an algorithm visualization environment for educational purposes. We discuss the results as occurred in the context of a web-based collaboration activity in the "algorithms analysis", computer science course. For this purpose we have designed and implemented AlCoLab, a web based environment, which provided the platform for our project. In the course of the activity, students interacted with the AV tool and followed the steps of a collaboration script, which led them to play roles as tutors and tutees, setting key questions and urge them to discuss critical issues on the subject of the merge sort algorithm. Based on our literature research on AV systems and CSCL, we claim, as the outcome of our case study illustrates, that an embedded instructional component, which enables student collaboration, is adequate to direct the students' interactions and dialogues on task related subjects and advance the process of algorithms' teaching. Additionally it provided useful information to improve the effectiveness of the AlCoLab tool.